Scope Of Nursing And Midwifery Practice In Saudi Arabia (The Review of Diabetic Studies, 2024)
Introduction: Saudi Healthcare Sector Transformation Program, which is part of Vision 2030, requires maximum use of nursing and midwifery workforce to propel the national transformations on preventative quality care. The official scope of practice is specified by the Saudi Commission of Health Specialties (SCFHS), and it is a crucial factor in the professional accountability and safeguarding of the population as well as enhancing patient safety. Nevertheless, transferring these high-level regulatory requirements into enforceable clinical practice has been an issue that cannot be solved at the systemic level.Study Objective: The objective is to assess the current state of nursing and midwifery and identify the gaps and challenges faced by these professions, and then to provide recommendations to improve nursing and midwifery.   Methodology: The analysis of the key regulatory documents of the SCFHS (official Scope of Practice document and domains of competence) and the Ministry of Health (MOH) standards was carried out using a systematic review approach. The review is based on the research published in the past and, in particular, looks at the barriers to the complete implementation of the scope concerning professional autonomy, adoption of Evidence-Based Practice (EBP), and workforce capacity. It compares the effectiveness in regulation that has led to limited prescriptive authority in the midwives with the legal limitations to the Advanced Practice Nursing (APN) positions..Conclusion: The official scope gives a strong basis to the advanced practice, but its use is highly limited by three systemic problems that are closely interrelated. Examples of these limitations are: 1) a national shortage of practitioners, especially midwives, that is critical; 2) widespread organizational opposition and hierarchical cultures that inhibit professional autonomy and the use of EBP, which has been documented as yet to be established; and 3) regulatory ambiguity that surrounds the legal authority of Advanced Practice Nursing (APN) roles.